Perlindungan Hukum Terhadap PT. Pos Indonesia Dalam Perjanjian Kerjasama Kemitraan Dengan Agen Pos Indonesia (Studi Kasus DI PT. Pos Indonesia Kantor Cabang Utama Denpasar) - Lia Siti Sawaliah; Ni Luh Made Mahendrawati; I Made Arjaya (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to examine the implementation of the partnership agreement between the Indonesian Pos Agent and PT Pos Indonesia (Persero) as well as the legal protection provided to PT. Pos Indonesia if there is a default from the postal agent. The research method used is an empirical legal method with a Fact, Sociological and Legislative approach. The results of this study indicate that the implementation of the partnership cooperation agreement between Pos Indonesia agents and PT Pos Indonesia (Persero) faces several problems, both in the operational and non-operational sections. One of the problems outside of operations is an error in the weight of the scales made by the postal agent which causes losses. In this case, PT. Pos Indonesia is given preventive and repressive legal protection. Preventive legal protection is carried out to prevent negligence, while repressive legal protection is carried out through reprimands, sanctions and compensation until the termination of the agreement permanently.